Distribution of Glyphosate-Resistance in Echinochloa crus-galli Across Agriculture Areas in the Iberian Peninsula - Vázquez-García, José G.; Rojano-Delgado, Antonia M.; Alcántara-de la Cruz, Ricardo; Torra, Joel; Dellaferrera, Ignacio; Portugal, João; De Prado, Rafael (Frontiers in Plant Science, 2021)
Greenhouse and laboratory studies were conducted to assess the levels of resistance to glyphosate of 13 barnyard grass (Echinochloa crus-galli) populations harvested across different agriculture areas in the Southern Iberian Peninsula. Shikimate accumulation fast screening separated the populations regarding resistance to glyphosate: susceptible (S) E2, E3, E4, and E6 and resistant (R) E1, E5, E7, E8, E9, E10, E11, E12 and E13. However, resistance factor (GR50 E1 to E13/ GR50 E6) values separated these populations into three groups: (S) E2, E3, E4, and E6, (R) E1, E5, E7, E8, E9 and very resistant (VR) E10, E11, E12 and E13. 14C-glyphosate assays performed on two S populations (E2 and E6) showed greater absorption and translocation than those found for R (E7 and E9) and VR (E10 and E12) populations. No previous population metabolized glyphosate to amino methyl phosphonic acid (AMPA) and glyoxylate, except for the E10 population that metabolized 51% to non-toxic products. The VR populations showed two times more EPSPS activity in the absence of glyphosate than the rest, while the concentration of glyphosate required to inhibit EPSPS activity by 50% (I50) was much higher in R and VR populations than in S populations. These results indicated that different non-target-site and target-site resistance mechanisms are involved in the levels of resistance of E. crus-galli to glyphosate. Our results conclude that resistance is independent of climate, type of crop, and geographic region and that the level of resistance to glyphosate is mainly due to the selection pressure of the herbicide exerted on the different populations of E. crus-galli studied.